Impact of interventions at Lima downtown since its Cultural Heritage of Humanity declaration - Rodríguez Larraín Echecopar, Mónica (2018)
The current impact of interventions performed on the urban tissue and either built or buildable areas, regarding the authenticity degree of the Historic Center of Lima, which is analyzed through the subsistence of urban, architectural, social, cultural and historical indicators that led to its Declaration of Cultural Heritage of Humanity, does not prove positive results in its conservation since 1991.